Search with multi-worker firms - William B. Hawkins; Daron Acemoglu (Theoretical Economics, 2014)
We present a generalization of the standard random-search model of unemployment in which firms hire multiple workers and in which the hiring process is time-consuming as well as costly. We follow Stole and Zwiebel (1996a,b) and assume that wages are determined by continuous bargaining between the firm and its employees. The model generates a non-trivial dispersion of firm sizes; when firms' production technologies exhibit decreasing returns to labor, it also generates wage dispersion, even when all firms and all workers are ex ante identical. We characterize the steady-state equilibrium and show that, with a suitably chosen distribution of ex ante heterogeneity across firms, it is consistent with several important stylized facts about the joint distribution of firm size, firm growth, and wages in the U.S. economy. We also conduct a numerical investigation of the out-of-steady state dynamics of our model. We find that the responses of unemployment and of the vacancy to unemployment ratio to a shock to labor productivity can be somewhat more persistent than in the Mortensen-Pissarides benchmark where each firm employs a single worker.
Keywords: E24; E32; J31; J64; 330; Bargaining; labor market dynamics; persistence; search; wages